Secondary School Teachers' Development In TPACK, ICT Literacy and High-Level Thinking: Community Service In SMK N 3 Purwokerto, Central Java - Wanda Nugroho Yanuarto; Ira Hapsari; Laily Nurlina; Mohamad Ikram Zakaria (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Students can gain a better grasp of subjects through the use of ICT literacy. Students can learn a wide range of facts and concepts in a balanced and effective way if they are literate in the use of information and communication technologies. Research has shown that there is a strong correlation between PLT and ICT Literacy. The correlation between TPACK and ICT literacy is strong as well. All of this points to the importance of TPACK, PLT, and ICT literacy as cornerstones of effective classroom instruction. The goals of this community service project are threefold: first, to increase teachers' TPACK competency, ICT literacy, and PLT understanding and knowledge; second, to develop TPACK competency programs; and third, to develop TPACK competency, ICT literacy, and PLT teaching materials. The author argues that the training implementation method is the most justified of the three prerequisites that any school must meet. These prerequisites include: 1) Setting up a system for online instruction. Naturally, their e-learning platform can cleanly display TPACK competencies, ICT literacy, and PLT; 2) Creating activities for innovation workshops; 3) Engaging students in learning TPACK competences, ICT literacy, and PLT through student-led activities.